Luteolin protects against adipogenic and lipogenic potency induced by human relevant mixtures of persistent organic pollutants (POPs) in the 3T3-L1 model. (March 2023) - Xie, Y.; Berntsen, H.F.; Zimmer, K.E.; Ropstad, E.; Verhaegen, S.; Connolly, L.
Abstract: Human exposure to persistent organic pollutants (POPs) may contribute to obesogenic effects. We have previously shown that POP mixtures modelled on blood levels relevant to the Scandinavian population induces adipogenic effects in the mouse 3T3-L1 cell line. Luteolin is a flavone that has shown anti-lipogenic and anti-adipogenic effects on adipogenesis in in vitro models. In this study, luteolin has been applied to inhibit adipocyte formation and intracellular lipid content increase induced by a human relevant mixture of POPs. 3T3-L1 cells were exposed to a POP mixture consisting of 29 chemicals, including amongst others polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), perfluoroalkylated acids (PFAAs), and polybrominated diphenyl ethers (PBDEs). Rosiglitazone was applied as a positive lipogenic control. Luteolin was tested between 0.5 and 10 μM. High content analysis was used to assess changes in adipocyte formation and intracellular lipid content in the 3T3-L1 cell line. Luteolin significantly reduced POP-induced adipocyte formation at 2, 5 and 10 μM, and lipid accumulation at 10 μM. Interestingly, luteolin did not affect rosiglitazone induced adipo- and lipogenic effects, suggesting differences in mechanisms of action. In conclusion, this in vitro study shows that dietary polyphenols such as luteolin may protect against POP induced adipo- and lipogenic effects.